How Risk Perceptions Influence Evacuations from Hurricanes and Compliance with Government Directives. Issue 2 (1st May 2013) - Stein, Robert; Buzcu‐Guven, Birnur; Dueñas‐Osorio, Leonardo; Subramanian, Devika; Kahle, David
<x xml:space="preserve">Abstract</x> In this study we present evidence supporting the view that people's perceived risk of hurricane‐related hazards can be reduced to a single seriousness score that spans different hurricane‐induced risk types and that compliant behavior with official advisories is strongly dependent on whether one perceives a high risk with respect to any type of hurricane‐related hazards. Our analysis suggests that people are less sensitive to risk type than they are to the general seriousness of the risks. Using this single seriousness score, representing a composite risk measure, emergency managers can be informed about the severity of the public's risk perceptions to impending hurricane hazards and might better craft their public directives in ways that minimize disruptive evacuations and achieve greater compliance with government directives.